A gene encoding lysine 6-aminotransferase, which forms the beta-lactam precursor alpha-aminoadipic acid, is located in the cluster of cephamycin biosynthetic genes in Nocardia lactamdurans. - Coque, J J (1991)
A gene (lat) encoding lysine 6-aminotransferase was found upstream of the pcbAB (encoding alpha-aminoadipylcysteinyl-valine synthetase) and pcbC (encoding isopenicillin N synthase) genes in the cluster of early cephamycin biosynthetic genes in Nocardia lactamdurans. The lat gene was separated by a small intergenic region of 64 bp from the 5' end of the pcbAB gene. The lat gene contained an open reading frame of 1,353 nucleotides (71.4% G + C) encoding a protein of 450 amino acids with a deduced molecular mass of 48,811 Da. Expression of DNA fragments carrying the lat gene in Streptomyces lividans led to a high lysine 6-aminotransferase activity which was absent from untransformed S. lividans. The enzyme was partially purified from S. lividans(pULBS8) and showed a molecular mass of 52,800 Da as calculated by Sephadex gel filtration and polyacrylamide gel electrophoresis. DNA sequences which hybridized strongly with the lat gene of N. lactamdurans were found in four cephamycin-producing Streptomyces species but not in four other actinomycetes which are not known to produce beta-lactams, suggesting that the gene is specific for beta-lactam biosynthesis and is not involved in general lysine catabolism. The protein encoded by the lat gene showed similarity to ornithine-5-aminotransferases and N-acetylornithine-5-aminotransferases and contained a pyridoxal phosphate-binding consensus amino acid sequence around Lys-300 of the protein. The evolutionary implications of the lat gene as a true beta-lactam biosynthetic gene are discussed.